Preventive treatment for migraine in primary care, a population-based study in the Netherlands. (October 2013) - Dekker, F; Dieleman, JP; Neven, A Knuistingh; Ferrari, MD; Assendelft, WJJ
Background: Preventive treatment of migraine contributes to reducing the impact of migraine but its extent of use in routine care is unknown. Objective: The objective of this article is to assess current use, previous use, duration and course of preventive treatment of migraine in Dutch general practice. Methods: We conducted a retrospective cohort study, for the period between 1997 and 2007, in the Interdisciplinary Processing of Clinical Information (IPCI) database, a GP research database in the Netherlands (source population of more than half a million subjects). All prevalent and incident migraine patients ( N = 7367) were included. Results: About 13% of all migraine patients currently use preventive therapy and almost half of migraine patients have prior use. Of those starting with preventive treatment, 56% (95% CI: 54.3–64.7) still used it after nine months. There was a long delay between migraine diagnosis and preventive treatment start. Forty-four percent (95% CI 43.0–45.7) started preventive therapy in the study period. Conclusion: This large primary-care database study shows that a limited number of patients are current users of preventive treatment, but many patients have prior use. After diagnosis there is often an extended time before preventive treatment is applied. Also there is often only one attempt. The continuation in time seems appropriate. Preventive therapy in migraine still deserves focus.